Application of ZnO‐Al2O3 Nanocomposite as Nanocatalyst for Photodegradation of Acid Violet 5B. Issue 5 (17th April 2015) - Karami, Hassan; Karimi, Mohammad Ali; Jokar, Raheleh
Abstract ZnO‐Al2O3 nanocomposite (ZANC) is used as nanocatalyst for photodegradation of acid violet 5B (AV5B) as an industrial dye. The experimental data shows that the degradation of AV5B is accelerated by ZANC and UV light. The effects of various parameters such as pH, hydrogen peroxide and ethanol are investigated on the photodegradation efficiency. Photocatalytic degradation rate of AV5B is increased by ethanol and hydrogen peroxide. Based on the kinetic studies, the rate constant of the photodegradation reaction is estimated 2.829 × 10‐1 min‐1.